Nikah Beda Agama Dalam Pandangan Liberalis dan Peraturan Perkawinan di Indonesia - Baharudin Ahmad (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2010)
This paper examines the liberal muslim intelectuals view on inter-religious marriage, arguing that liberal muslim's judgment on the legality of inter-religious marriage is in contradiction with the pronouncement of the exiting state law on marriage such as no 1 tahun 1974, no 9 tahun 1075 and the state compilation of islmaic law (Komilasi Hukum Islam), furthermore,using islamic legal reasoning, the paper staress that the disadvantages (mudarat) of inter-religous marriage overmeigh its advantages (maslahah) and therefore argues again is legality as proposed by liberal muslim intelectuals.